A hydrophobic loop in acyl-CoA binding protein is functionally important for binding to palmitoyl-coenzyme A: A molecular dynamics study - Vallejo, Diego Fernando Gustavo (2008)
Acyl-CoA binding protein (ACBP) plays a key role in lipid metabolism, interacting via a partly unknown mechanism with high affinity with long chain fatty acyl-CoAs (LCFA-CoAs). At present there is no study of the microscopic way ligand binding is accomplished. We analyzed this process by molecular dynamics (MDs) simulations. We proposed a computational model of ligand, able to reproduce some evidence from nuclear magnetic resonance (NMR) data, quantitative time resolved fluorometry and X-ray crystallography. We found that a hydrophobic loop, not in the active site, is important for function. Besides, multiple sequence alignment shows hydrophobicity (and not the residues itselves) conservation.